2022
DOI: 10.1021/acsaelm.1c00992
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and Rashba Spin–Orbit Coupling in the Two-Dimensional (V,Pt)Se2 Alloy

Abstract: We report on a two-dimensional (2D) V1–x Pt x Se2 alloy that exhibits ferromagnetic order and Rashba spin–orbit coupling. Although ferromagnetism is absent in 1T-VSe2 because of the competition with the charge density wave phase, we demonstrate theoretically and experimentally that the substitution of vanadium by platinum in VSe2 (10–50%) to form a homogeneous 2D alloy restores ferromagnetic order down to one monolayer of V0.65Pt0.35Se2. Moreover, the presence of platinum atoms gives rise to Rashba spin–orbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…, 1T-VSe 2 18 and MnSe 2 , 17 have been also reported being magnetic in some of their crystallographic phases or as a result of doping. 437 Ising-type magnetic ordering has also been demonstrated in phosphorus-based insulating antiferromagnets, e.g. , in FePS 3 .…”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 99%
“…, 1T-VSe 2 18 and MnSe 2 , 17 have been also reported being magnetic in some of their crystallographic phases or as a result of doping. 437 Ising-type magnetic ordering has also been demonstrated in phosphorus-based insulating antiferromagnets, e.g. , in FePS 3 .…”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 99%
“…Measurements on the (presumably disordered) 2D VxPt1-xSe2 alloys confirmed the presence of magnetism at low temperature in MBE grown layers down to the monolayer limit [22]. Specifically, a ferromagnetic order sets-in below 10-30 K in the monolayer phase for x=0.35 [22].…”
Section: Introductionmentioning
confidence: 72%
“…Further ab-initio calculations have indeed shown that monolayers of ordered 1T-VxPt1-xSe2 alloys could be ferromagnetic for 0.1<x<0.5 [22], even when the lattice deformation associated with the CDW state was taken into account. Measurements on the (presumably disordered) 2D VxPt1-xSe2 alloys confirmed the presence of magnetism at low temperature in MBE grown layers down to the monolayer limit [22]. Specifically, a ferromagnetic order sets-in below 10-30 K in the monolayer phase for x=0.35 [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations